(3fgGjI GdCQH aj CNHGQ GdYQHs - (3EScfOQ Hf jYbhH CHcGQjhS GdCQefj,J (B1303 (3g` s
(3ChdgG (B:s
(3CeG HYO Efi deG QCjJ EbHGd GdfGS ai OjGQfG GdTGejI Edi eYQaI CNHGQ GdYQH GdLGgdjI, TeQJ Yf SGYO GdYRe hGdLgGO, Edi GdJbGWgG ef cd TYH hhGO s
(3BNQgG (B:s
(3JeJ GdeYdbGJ , hgPG BNQ GdMcGjGJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B304 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B253s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B461 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs